Penerapan Digital Marketing Sebagai Strategi Pemasaran Serta Membangun Brand Awareness pada UMKM Rengginang GR Wedoro - Marjiatul Maghfiroh; Nur Rahmawati (Universitas Kristen Indonesia Toraja, 2024)
MSMEs have a large contribution to the Indonesian economy both at the micro and macro level. In carrying out their operations, of course MSMEs have their own advantages and disadvantages. Rengginang GR Wedoro MSMEs face challenges in building brand awareness among their target market. The technology that has been implemented by MSME Rengginang GR Wedoro is still considered very minimal, namely only using WhatsApp and Instagram which are still not optimal. This means that MSMEs cannot reach consumers optimally. The data collection method applied involves two main approaches, namely observation and interviews. The results of the current use of digital marketing, Rengginang GR Wedoro MSMEs use websites, Instagram, TikTok and Facebook as marketing media because they are platforms that have quite a large number of users in Indonesia. The use of social media has a significant impact on increasing brand awareness of Rengginang GR MSMEs. . It is important to manage social media accounts effectively by providing quality content, interacting with audiences, and tracking performance metrics to continuously improve the marketing strategies implemented